Innovations in Quantitative Risk Management TU München, September 2013 - Glau, Kathrin; Scherer, Matthias; Zagst, Rudi (Springer Proceedings in Mathematics & Statistics,, 2015)
Quantitative models are omnipresent -but often controversially discussed- in todays risk management practice. New regulations, innovative ﬁnancial products, and advances in valuation techniques provide a continuous ﬂow of challenging problems for ﬁnancial engineers and risk managers alike. Designing a sound stochastic model requires ﬁnding a careful balance between parsimonious model assumptions, mathematical viability, and interpretability of the output. Moreover, data requirements and the end-user training are to be considered as well. The KPMG Center of Excellence in Risk Management conference Risk Management Reloaded and this proceedings volume contribute to bridging the gap between academia -providing methodological advances- and practice -having a ﬁrm understanding of the economic conditions in which a given model is used. Discussed ﬁelds of application range from asset management, credit risk, and energy to risk management issues in insurance. Methodologically, dependence modeling, multiple-curve interest rate-models, and model risk are addressed. Finally, regulatory developments and possible limits of mathematical modeling are discussed.